Preferences, Partners, and Parenthood: Linking Early Fertility Desires, Union Formation Timing, and Achieved Fertility - Natalie Nitsche; Sarah Hayford (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2018)
"Underachieving" fertility desires is more common among women with higher levels of education and those who delay the first marriage beyond the mid-twenties. However, the relationship between these patterns, in particular the degree to which marriage postponement explains lower fertility among the highly educated, is not well understood. In this paper, we use data from the National Longitudinal Survey of Youth-1979 cohort to analyze differences in parenthood and achieved parity for men and women, focusing on the role of union formation timing in achieving fertility goals over the life course. We expand on previous research by distinguishing between entry into parenthood and average parity among parents as pathways to underachieving; by considering variation in the impact of marriage timing by education and by stage of the life course; and by comparing results for men and women. We find that the most educated women who desired three or more children are less likely to become mothers both relative to less-educated counterparts who desired large families and relative to their college-educated peers desiring two children. Once they achieve motherhood, however, they do have the highest average parity. No comparable fatherhood differential by desired family size is present. Postponing marriage beyond the age of 30 is associated with decreases in parenthood and average parity. Age patterns are similar for both women and men, pointing at social rather than biological factors for the underachievement of fertility goals.
Keywords: 300; Fertility; fertility desires; marriage; education